The effects of inter- and intra-cultural variations on managerial discretion and the implications for national competitiveness - Haj Youssef, Moustafa (2017)
This thesis examines cross-cultural differences in managerial discretion and the extent to which variations in inter- and intra-cultural practices affect the degree of freedom in decision-making that is afforded to executives. Research into the degree of discretion, or ‘latitude’ of executive action, has primarily focused on individual-, firm-, and industry-level factors which, either enable or otherwise constrain the freedom of executive action. However, research into its national-level antecedents and consequences remains limited. This thesis further develops and extends the extant literature into the topic of managerial discretion by seeking to adopt a broader interpretation of national culture in relation to its effect on executive discretion across 18 countries from 6 different regional clusters. The research entails a quantitative assessment to examine the relationship between cultural practices, managerial discretion and national competitiveness. The investigation into the national-level antecedents, consequences and the role of managerial discretion is studied using a mixture of primary and secondary data. Primary data consists of measurements of the degree of managerial discretion that is derived from survey responses of a panel of senior management consultants, who provided 792 discretion scores for the sampled countries. Secondary data consists of cultural practices derived from GLOBE cross-cultural project and national competitiveness scores operationalized using the Global Competitiveness Index (GCI). The thesis presents three empirical analyses of socio-cultural dynamics. The research first addresses how cross-national variations in cultural practices impact managerial discretion. The findings reveal that institutional collectivism, uncertainty avoidance, power distance, future-, humane-, and performance orientations, together with gender egalitarianism, assertiveness and cultural looseness, all influence the degree of discretion. In the second dimension, the notion that intra-cultural variation plays a crucial role in shaping managerial discretion is critically discussed. An empirical analysis supports such a proposition and demonstrates a strong and positive association between these two constructs. For the third aspect, the relationship between managerial discretion and national performance is measured and evaluated by determining the impact upon national competitiveness. The data demonstrate that the degree of discretion directly influences national competitiveness and effectively mediates the relationship between cultural practices and national competitiveness. Overall, this PhD contributes to the field of strategic management, by discovering for the first time new national-level antecedents and consequences of managerial discretion, offering new theoretical insights and practical implications.